The Impact of Fundamental Factors on the Share Price of Micro-Sized Nasdaq Listed Technology Companies - Rafaqat, Simon; Rafaqat, Sahil; Rafaqat, Saoul; Rafaqat, Dawood (The Economics and Finance Letters, 2021)
The paper aims to examine the impact of fundamental factors on the share price of the companies in the sector of technology. Therefore, the study has selected eighteen micro-size technology companies listed in NASDAQ with a market capitalization between $50 million and $300 million. The data have been obtained from these companies’ annual reports, NASDAQ, and SEC ranging from 2015 to 2019. The study evaluates the influence of firm size, earning per share, debt equity ratio, current ratio, operating cash flow ratio, return on equity, assets turnover ratio, return on assets, and the net profit margin on the share price of the selected companies. Moreover, the study uses multiple regression analysis, ANOVA, Pearson correlation, normality, multicollinearity, heteroscedasticity, autocorrelation test to find the effect of predictor variables on the share price. The results show that the operating cash flow ratio has a positive insignificant effect while debt equity ratio, net profit margin, and return on equity have a negative insignificant impact on the share price. However, return on assets, earning per share, and firm size have a positive significant relationship with share price, whereas the current ratio and the asset turnover ratio have a negative significant relationship with the share price. In conclusion, although the variables have a more negative insignificant effect than the positive insignificant impact on the share price, the variables have a more positive significant effect than a negative significant influence. Overall, the fundamental factors collectively have a significant impact on the share price of the experimented companies.